Urinary metabolomics of complete Freund's adjuvant‐induced hyperalgesia in rats. (5th January 2017) - Liu, Yang; Chen, Hui; Lu, Jun; Jiang, Youshui; Yang, Rui; Gao, Songyan; Dong, Xin; Chen, Wei
Abstract: The aim of this study was to demonstrate the differences of metabolomics changes in a hyperalgesia model and find potent biomarkers of hyperalgesia. Seven rats were placed in metabolic cages. An emulsion containing 500 μg of Complete Freund's adjuvant (CFA) was used to induce hyperalgesia. Urine samples were collected prior to the injection of CFA and on post‐injection days 1, 3 and 7. Ultraperformance liquid chromatography, coupled with quadrupole‐time‐of‐flight mass spectrometry (UHPLC‐Q‐TOF/MS), was used for a quantitative analysis of urinary metabolic changes in the CFA‐induced hyperalgesia model. Differences between the metabolic profiles of the rats in the four groups were analyzed using partial least squares discriminant analysis. Thirty‐four potential urine metabolite biomarkers were identified, which changed in a trend similar to the pain threshold. These potential biomarkers were involved in 11 metabolic pathways, as follows: alanine, aspartate, and glutamate metabolism; ascorbate and aldarate metabolism; glycerolipid metabolism; glycerophospholipid metabolism; histidine metabolism; phenylalanine metabolism; sphingolipid metabolism; tryptophan metabolism; tyrosine metabolism; valine, leucine and isoleucine biosynthesis; and vitamin B6 metabolism. These results may improve our understanding of hyperalgesia and provide a basis for the clinical diagnosis of hyperalgesia.